The First decision of amparo in Mexico. (An antecedent of constitutional history) - Palomino Manchego, José F. (2012)
We realize the first amparo judgement in the history of the constitutional law, which was pronounced in Mexico, and we also analyze the three successive periods through which this amparo proceedings has passed in the historical context of the 19th century, as well as its subsecuent development and regulation